Characterization of superoxide-stress sensing recombinant Escherichia coli constructed using promoters for genes zwf and fpr fused to lux operon - Niazi, Javed H.; Kim, Byoung Chan; Gu, Man Bock (Springer Verlag, 2007)
To measure the toxicity experienced by superoxide-generating compounds, two plasmids were constructed in which the superoxide-inducible fpr and zwf promoters from Escherichia coli were fused to promoterless Vibrio fischeri luxCDABE operon present in plasmid pUCD615. The bioluminescent response of E coli harboring these constructs was studied as a function of the toxicity and was shown to be specific for superoxide generating chemicals. The two promoters employed, fpr and zwf, responded differentially to the redox-chemicals tested. Furthermore, a Delta marA strain bearing the fpr::luxCDABE fusion had a weaker response to paraquat (methyl viologen) than its isogenic parent strain, whereas zwf induction was not inhibited in Delta marA or Delta rob strains. The fpr and zwf promoters were also induced by alkylating agents but were unresponsive in Delta marA or Delta rob strains. Using optimized assay conditions, the abilities of these strains to differentially respond to superoxide stress and alkylating agents that may be present in contaminants proves them to be good biosensor candidates for monitoring toxicity.